The effect of titanium oxide and hydroxyapatite on the mechanical properties of wollastonite. Issue 1 (1st January 2019) - Ragurajan, D.; Satgunam, M.; Golieskardi, M.; Sankar, U.; Ng, Angela Min Hwei
Abstract: The effect of incorporation of titanium oxide (TiO2 ) and hydroxyapatite (HA) on the mechanical properties of wollastonite (CaSiO3 ) was investigated in this study. TiO2 /CaSiO3 /HA composites were prepared and characterized by means of physical and mechanical properties. Morphology analysis revealed that the wollastonite composite possesses a rough surface. Moreover, the addition of TiO2 and HA to wollastonite was evaluated by means of bulk density and Vickers Hardness. The wollastonite composites containing TiO2 (10–30 wt%) and HA (20–40 wt%) were sintered between 1230°C and 1270°C, with a ramp rate of 10°C/min and a holding time of 2 h. The results indicated that the additives played a significant part in enhancing the physical and mechanical properties of the composite wollastonite in comparison to the pure wollastonite, particularly in composites containing higher percentage of TiO2 (25–30 wt%) and lower HA (20–25 wt%). Furthermore, the results obtained from the XRD analysis revealed that the newly formed apatite particles on the surface of the wollastonite composite were comprise of superfine crystalline and/or defective structure grains.